2014
DOI: 10.1097/inf.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Safety Monitoring After Rotavirus Vaccine Implementation

Abstract: Mortality due to intussusception was high among Rwanda children. Delays in presentation and treatment were common. Assessing trends in the number of cases to monitor for vaccine-associated intussusception will be difficult. Additional work is needed to further understand risk factors for mortality, to calculate incidence rates and to monitor the safety of the rotavirus vaccination program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…We describe the results of over four years of active hospital-based surveillance for intussusception in all 7 seven divisions in Bangladesh. The proportion of males diagnosed with intussusception was higher than that of females, which is consistent with other reported data on intussusception cases occurring in the absence of rotavirus vaccine administration from both high and low income settings [1722]. The reasons for this male predominance are unclear but may reflect greater healthcare seeking for male children with intussusception, genetic factors or both.…”
Section: Discussionsupporting
confidence: 88%
“…We describe the results of over four years of active hospital-based surveillance for intussusception in all 7 seven divisions in Bangladesh. The proportion of males diagnosed with intussusception was higher than that of females, which is consistent with other reported data on intussusception cases occurring in the absence of rotavirus vaccine administration from both high and low income settings [1722]. The reasons for this male predominance are unclear but may reflect greater healthcare seeking for male children with intussusception, genetic factors or both.…”
Section: Discussionsupporting
confidence: 88%
“…In Rwanda, findings from retrospective study on HAI conducted at University Teaching Hospital of Kigali indicated that SSI account for 76.8% of all HAIs in surgical department and that 35% of children with SSI experienced complications [13]. However, data are lacking the incidences of SSI until 30 days-post operation including discharged patients before that period making difficult to estimate the really burden of SSI.…”
Section: Introductionmentioning
confidence: 99%
“…A review of Zambian hospitals of IS in children <24 months old showed a high CFR of 33.7% 28 . In Rwanda, delays in presentation and treatment of IS resulted in the 28% mortality rate 29 . Overall, in African countries, the delayed presentation was common and 87% of cases required surgical intervention with a high CFR of 10 to 33.7% 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%